Teknologi Tepat Guna Pemanfaatan Listrik Daya Kecil untuk Pengelolaan Kandang pada Budidaya Ayam Pedaging di Desa Pucangsongo Kabupaten Malang - Andriani Parastiwi; Mila Fauziyah; Dwi Puspitasari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
One of the problems faced by small-scale broiler cultivators in Pucangsongo-Malang was the use of PLN electricity that exceeds the installed capacity. Partners feel it was too expensive to raise the power capacity. To overcome the problem, timing settings to power the equipment is needed. The cage-smell’ problem needs to be handled because the cage-locations are in settlement. The purpose of this activity was helping partners to increase productivity by helping solve problems from production aspects, as well as the safety. The implementation method was providing appropriate science and technology to partners in the form of electricity utilization management equipped with a cage monitoring system. In addition, it also developed a backup power source safety system that works when the electricity goes off to keep the cage remain conducive. Prior this activity, the cage-capacity was 3300 with an average death of 200 chickens. Currently, the cage-capacity increased to 3500 chickens with deaths down to 110 chickens. With the developed and installed electric power management equipped with monitoring system of cage condition, broiler cultivators in Pucangsongo-Malang can monitor the cage’s state at any time and power shortage problem can be resolved.